2016
DOI: 10.3171/2015.2.jns142318
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Alzheimer’s pathology in patients with clinical normal pressure hydrocephalus: correlation of high-volume lumbar puncture results, cortical brain biopsies, and outcomes

Abstract: abbreviatioNs AD = Alzheimer's disease; CERAD = Consortium to Establish a Registry for Alzheimer's Disease; CSF = cerebrospinal fluid; GDS = Global Deterioration Scale; HVLP = high-volume lumbar puncture; NPH = normal pressure hydrocephalus. obJective Normal pressure hydrocephalus (NPH) remains most often a clinical diagnosis and has been widely considered responsive to the placement of a cerebrospinal fluid (CSF) shunt. The high incidence of patients with Alzheimer's disease (AD) with NPH symptoms leads to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 23 publications
9
64
1
3
Order By: Relevance
“…Another example is that of a patient being considered for ventriculoperitoneal shunting for suspected normal pressure hydrocephalus. AD is the most frequent reason for therapeutic failure 127 so a biomarker test indicating the presence of AD pathology may help avoid unnecessary surgery. Whether or not an older patient with clinically probable AD should also undergo biomarker testing to further enhance diagnostic confidence is less clear.…”
Section: Unresolved Clinical Questions: Diagnosismentioning
confidence: 99%
“…Another example is that of a patient being considered for ventriculoperitoneal shunting for suspected normal pressure hydrocephalus. AD is the most frequent reason for therapeutic failure 127 so a biomarker test indicating the presence of AD pathology may help avoid unnecessary surgery. Whether or not an older patient with clinically probable AD should also undergo biomarker testing to further enhance diagnostic confidence is less clear.…”
Section: Unresolved Clinical Questions: Diagnosismentioning
confidence: 99%
“…In our study, the absence of Ab or HPs pathology in the frontal cortical biopsy predicted the HRQoL outcome 1 year after the shunting (Fig. S1), which is logical, as the neurodegenerative comorbidities [7][8][9][10] and patients' old age [6,7] are associated with poorer outcome (Fig. S2, Table S3).…”
Section: Discussionmentioning
confidence: 54%
“…Other neurodegenerative diseases, such as Alzheimer's, vascular dementia, and Parkinson's diseases, are also common in the same age population. Studies have shown coexistence of increased rate of Alzheimer's disease (AD) histopathology in patients with iNPH beyond what can be accounted for by chance alone . Studies have shown decrease CSF production and turnover in both AD and NPH .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown coexistence of increased rate of Alzheimer's disease (AD) histopathology in patients with iNPH beyond what can be accounted for by chance alone. 6,7 Studies have shown decrease CSF production and turnover in both AD and NPH. 8 It was postulated by Silverberg that failure of CSF production or increased CSF flow resistance might lead to either AD, iNPH, or AD-NPH depending on which pathological process predominates.…”
Section: Introductionmentioning
confidence: 99%